Pengaruh Employees Burnout Terhadap Kepuasan Kerja Karyawan di Rumah Sakit Jiwa (RSJ) Sambang Lihum - Anita Putri Fatonah; Eny Hastuti; Andri Nur Rahman; Reny Marliadi (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2024)
The influence of Employees Burnout on employee job satisfaction is a problem that can increase the risk of fatigue and thus affect the level of employee job satisfaction. A high level of job satisfaction has fewer opportunities to quit work, while Employees who have a lower level of satisfaction will cause stress or work fatigue so that they have the potential to leave their job/quit working. This research aims to analyze the influence of employee Burnout on the job satisfaction of Employees who work at the Sambang Lihum Mental Hospital (RSJ). This research is quantitative research. This research took samples using random sampling techniques. The instrument used in the research is a questionnaire containing structured questions to measure each variable studied. The results of this research show that Employees working at RSJ Sambang Lihum experienced 2.5% Burnout with a high level of job satisfaction of 79.3%.